PENGARUH PENERAPAN MODEL BLENDED LEARNING TERHADAP PRESTASI BELAJAR SEJARAH SISWA - Arif Permana Putra (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2015)
The method uses in this research is experimental method. The sample data acquired using multi stage sampling technique. Analysis data technique uses two way anava. The results of the research are: (1) there are significant effects in the using of blended learning method and interactive approach on the historical major students’ achievement (Fcomputing > Ftable or 17,320 > 3,11); (2) there is no significant effect on the historical major students’ achievement between IPS and IPA (Fcomputing < Ftable or 0,060 < 3,11); and (3) learning approach and the historical major students’ achievements, it can be seen by the result (Fcomputing < Ftable atau 0,405 < 3,11).